2019
DOI: 10.1167/tvst.8.3.47
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Glaucoma Drugs Latanoprost and Brimonidine on Corneal Temperature

Abstract: Purpose The aim of this study was to investigate the effects of the glaucoma drugs latanoprost, brimonidine, and the combination of both on the central corneal temperature (CT) of healthy subjects by means of infrared thermography. Changes of the central CT may reflect changes of ocular blood flow. Methods Before application and during 2 hours after the application of latanoprost, brimonidine, or the combination of both in one eye, the CT in both eyes of 40 healthy subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…27 Current use of topical glaucoma treatment did not have a significant effect on OST and there were no significant differences due to the use of different eyedrop types. Our findings are partially supported by Konieczka et al, 28 who observed that latanoprost eyedrops had a very small and insignificant influence on the OST, and that brimonidine reduced the OST by approximately 0.5°C.…”
Section: Discussionsupporting
confidence: 88%
“…27 Current use of topical glaucoma treatment did not have a significant effect on OST and there were no significant differences due to the use of different eyedrop types. Our findings are partially supported by Konieczka et al, 28 who observed that latanoprost eyedrops had a very small and insignificant influence on the OST, and that brimonidine reduced the OST by approximately 0.5°C.…”
Section: Discussionsupporting
confidence: 88%
“…We investigated the effect of glaucoma drugs on corneal temperature. After one drop of brimonidine, the temperature of the cornea dropped for approximately 90 min due to the vasoconstrictive effect of brimonidine [ 27 ], whereas we observed no cooling under placebo. Interestingly, this effect was significantly stronger in patients with FS than in patients without FS (CTR NCT01201551, publication in preparation).…”
Section: Drug Treatment Of Patients With Fsmentioning
confidence: 76%
“…There is also controversy regarding the relationship between corneal temperature and intraocular pressure (IOP) in patients with glaucoma since a study in healthy subjects showed that induced changes in corneal temperature (by increasing temperature after closing the eyelids for one hour) caused an IOP increase, and on the contrary, the use of a cooling mask induced a decrease in IOP that correlated with the decrease in corneal temperature [ 96 ]. Similarly, thermography provided indirect information about the influence of glaucoma medications; specifically, some antiglaucoma drugs have been shown to lower central corneal temperature at a time point coincident with their peak effect [ 97 ]; this supports the idea that OST may be elevated in patients with glaucoma.…”
Section: Use Of Thermography In Ophthalmologymentioning
confidence: 87%